PENJAMINAN MUTU PENGELOLAAN PERPUSTAKAAN SEKOLAH - Siti Rohmah (UNIVERSITAS BENGKULU, 2015)
The purpose of this study was to know the quality assurance management of the school library at Senior High School Number 2 Lubuklinggau. This study uses descriptive qualitativeresearch. Data collected by using interviews, observation and study documentation. Through this research note that the quality assurance management in the school library is being prepared by the school. Start of preparing a quality manual and quality policy of the school library management, work program and minimize the obstacles that arise in quality assurance management of the school library. The principal and head of the library is committed to creating quality assurance management of Senior High School Number 2 Lubuklinggau.Keywords: quality assurance, school library, management